A Literature Review of Transportation Logistics Policy Models in the Nusantara Capital City Region to Support National Economic Growth - Eko Agus Susanto; Muhammad Zilal Hamzah; Eleonora Sofilda (Dinasti Publisher, 2024)
The purpose of this study is to review and analyze several previous studies theoretically related to 1) The impact of Logistics Transportation Policy and spillover effects on National Economic Growth, 2) Some problems from the implementation of the Logistics Transportation Policy in a region, 3) Logistics Transportation Policy Model that can support National Economic Growth. The method used uses qualitative research, exploratory or interpretative systems with a systematic deductive process (Top-Down), guided by some empirical evidence obtained from the author's experience in the field of transportation and logistics, as well as qualitative interactions with several stakeholders and previous research. The results found are 1) in some countries, logistics policies have succeeded in having a positive impact on regional and national economic growth, 2) the ineffectiveness of a logistics policy is caused by high logistics costs, dysfunctional systems, unsupportive regulations, unsupportive human resources and infrastructure and weak coordination between stakeholders, and 3) a transportation logistics policy model that supports national economic growth must be able to involve stakeholders so that it can have a multiplier effect on the economic sector and national economic growth.